Development and characterization of 25 EST-SSR markers in Pinus sylvestris var. mongolica (Pinaceae)(1) - Fang, Pan (Botanical Society of America, 2014)
• Premise of the study: A set of novel expressed sequence tag (EST) microsatellite markers was developed in Pinus sylvestris var. mongolica to promote further genetic studies in this species. • Methods and Results: One hundred seventy-five EST–simple sequence repeat (SSR) primers were designed and synthesized for 31,653 isotigs based on P. tabuliformis EST sequences. The primer pairs were used to identify 25 polymorphic loci in 48 individuals. The number of alleles ranged from two to eight with observed and expected heterozygosity values of 0.0435 to 0.8125 and 0.0430 to 0.7820, respectively. • Conclusions: These new polymorphic EST-SSR markers will be useful for assessing genetic diversity, molecular breeding and genetic improvement, and conservation of P. sylvestris var. mongolica.